Fostering Creativity in the Classroom for High Ability Students: Context Does Matter - Liang See Tan; Shu Shing Lee; Letchmi Devi Ponnusamy; Elizabeth Ruilin Koh; Keith Chiu Kian Tan (MDPI AG, 2016)
Researchers have argued for the importance of the classroom context in developing students' creative potential. However, the emphasis on a performative learning culture in the classroom does not favour creativity. Thus, how creative potential can be realised as one of the educational goals in the classrooms remains a key question. This study measured creativity across three secondary schools using the Wallach-Kogan Creative Thinking Test (WKCT). A total of 283 students enrolled in the Express programme and 290 students enrolled in the Integrated Programme (IP) volunteered in the study. The same cohort of students took the 38-item WKCT twice; once at the beginning of Secondary One and then at the end of Secondary Three. Four aspects of creativity, namely fluency, flexibility, unusualness, and uniqueness, were investigated. Our analyses showed that (i) IP students showed a greater increase in scores over time when compared to Express students; (ii) when Programme and PSLE (Primary School Leaving Examination) were used to predict creativity scores in a multiple regression, the predictive power of Programme increased from Secondary 1 to Secondary 3 while that of PSLE decreased; and (iii) flexibility scores were more resistant to change than fluency scores. These findings suggest that the classroom context matters and that the removal of high-stakes examination can provide room for the development of creative potential.